A cultura popular sertaneja em José de Alencar e Juvenal Galeno - Manoel Carlos Fonseca de Alencar (2015)
This thesis analyzes the representations of Brazilian popular culture in José de Alencars and Juvenal Galenos works, from 1850 to 1920. Based on the concepts of appropriation, dialogue, historical perspective and narrative transculturation, we study the relationship that the authors established with the popular sectors, and how they depicted popular culture in their literary narratives. With regard to José de Alencar, we realized that the importance he gave to popular culture relates to his concern with the constitution of nationality. In this sense, the author made use of indigenous and "popular" traditions, always in dialogue with European writers, what made he change his understanding about the characters, the plots and the language that should subsidize the definition of cultural and literary independence of Brazil, constituting it as a distinct nation from the other ones. As for Juvenal Galeno, we investigate the dialogue that the author established with the cultured literature and the oral tradition of the popular sectors of the sertão. From his personal experience, we discuss the relationship that the author established with the poor sections of the sertão, which is an essential factor for the comprehension of the poet as a cultural mediator, who processed a culture of the oral forms with respect to the language, the poetic forms and the imagery.